2020
DOI: 10.32951/mufider.752097
|View full text |Cite
|
Sign up to set email alerts
|

İç Kontrol Si̇stemi̇ni̇n Kurumsallaşma Üzeri̇ne Etki̇si̇: Devlet Üni̇versi̇teleri̇ Üzeri̇ne Bi̇r Araştirma

Abstract: Kamu ya da özel sektör işletmelerinin yanı sıra üniversitelerde de kurumsallaşma ve iç kontrol kavramlarının önemi artmaktadır. Özellikle devlet üniversiteleri karşısında özel üniversite sayısının artması bu kavramların önemini daha da arttırmaktadır. Devlet üniversitelerinin özel üniversitelere karşı eğitim kalitesini, öğrenci sayısını ve kaliteli bilimsel yayınlarını arttırma konusunda başarı gösterebilmeleri için kurumsallaşma ve iç kontrol sistemi konularında ilerleme kaydetmeleri gerekir. Bu çalışmada, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…There is a bicycle path surrounding the park, a 6-car parking lot at the park entrance, and a bicycle park and vehicle parking pockets surrounding the park (Figure 4). Availability: According to Hacıhasanoğlu & Hacıhasanoğlu (1997), availability is defined as the ability of individuals to reach all places around them by themselves or with the help of any vehicle (Alpagut, 2003). In society, individuals have to perform some activities to live and integrate with their environment.…”
Section: Access and Linkagesmentioning
confidence: 99%
“…There is a bicycle path surrounding the park, a 6-car parking lot at the park entrance, and a bicycle park and vehicle parking pockets surrounding the park (Figure 4). Availability: According to Hacıhasanoğlu & Hacıhasanoğlu (1997), availability is defined as the ability of individuals to reach all places around them by themselves or with the help of any vehicle (Alpagut, 2003). In society, individuals have to perform some activities to live and integrate with their environment.…”
Section: Access and Linkagesmentioning
confidence: 99%
“…In the study of Bulut (2019), it was concluded that there is a highly positive and significant relationship between the institutionalization process and the internal control system at Karadeniz Technical University and that the internal control process has a positive effect on institutionalization. In the study of Hacıhasanoğlu and Çağlı (2020), it was revealed that there is a high level of relationship between the level of institutionalization of state universities and the internal control system and that the internal control system also has a significant effect on the level of institutionalization.…”
mentioning
confidence: 99%